The Influence of Islamic Financial Literacy on Behavior and Decisions to Invest in Gold Instruments - Mahmud, Muhammad Daud bin; Sudirman, Muh. Sajjaj; Jufri, Fahria (Faculty of Islamic Economics and Business Sultan Aji Muhammad Idris State Islamic University Samarinda, 2024)
This study aims to investigate how gold investing decisions and behavior are affected by Islamic financial literacy. From a population of 31,119 people, 100 respondents from Morotai Island Regency in North Maluku Province were selected as the sample using the purposive sampling technique, with a 0.05 error tolerance. By testing the outer model and inner model, partial least square-structural equation modeling is applied as a data analysis tool. Only 2 of the 9 indicators used to measure the proposed Islamic financial literacy variable met the requirements. Both investment decisions and behavior variable indicators have 3 and 4 qualified indicators, respectively. Several previous studies have used a general measure of financial literacy, but this study measures financial literacy with a specific Islamic financial literacy scale. The results of this study prove that Islamic financial literacy has a positive influence on a person's behavior and his/her decision to invest using gold investment instruments. People who are well-literate in Islamic finance will have an impact on their investing behavior, which will allow them to make wise investment decisions and improve their financial well-being.